2020
DOI: 10.3832/ifor3231-013
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal communities across land use types

Abstract: Biogeosciences and Forestry Biogeosciences and Forestry Soil fungal communities across land use types Sujan Balami (1) , Martina Vašutová (1-2) , Douglas Godbold (2-3) , Petr Kotas (4) , Pavel Cudlín (2) Land use change is one of the major causes of biodiversity loss, mostly due to habitat change and fragmentation. Belowground fungal diversity is very important in terrestrial ecosystems, however, the effect of land use change on soil fungal community is poorly understood. In this review, a total of 190 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 92 publications
(123 reference statements)
2
10
0
Order By: Relevance
“…In this study, we confirmed our hypothesis that the conversion of a temperate forest to arable land significantly decreased alpha, beta, and phylogenetic diversity of soil fungal communities, but only the beta diversity decreased when the forest was converted to pasture. Although the effect of deforestation on species richness and diversity can vary, they decrease mostly when a forest is converted to a cultivated system, such as a plantation, perennial cropland, or cropland (e.g., Balami et al, 2020 ). In this study, the decremental effect of land-use change on fungal diversity can be mainly attributed to changes in vegetation as none of the tested soil physicochemical properties correlated with changes in the fungal taxonomic and phylogenetic alpha diversity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirmed our hypothesis that the conversion of a temperate forest to arable land significantly decreased alpha, beta, and phylogenetic diversity of soil fungal communities, but only the beta diversity decreased when the forest was converted to pasture. Although the effect of deforestation on species richness and diversity can vary, they decrease mostly when a forest is converted to a cultivated system, such as a plantation, perennial cropland, or cropland (e.g., Balami et al, 2020 ). In this study, the decremental effect of land-use change on fungal diversity can be mainly attributed to changes in vegetation as none of the tested soil physicochemical properties correlated with changes in the fungal taxonomic and phylogenetic alpha diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi occupy a wide range of ecological niches 1 . Forest soil likely represents the largest reservoir of fungi 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Forest soil likely represents the largest reservoir of fungi 2 . Soil fungal communities perform a variety of essential functions and, hence, play a vital role in many forest ecosystem functions 1 . Saprotrophic fungi are mainly responsible for organic matter and plant litter decomposition and thereby influence nutrient cycling 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Fungi occupy a wide range of ecological niches (Balami et al, 2020). Forest soil likely represents the utmost reservoir of fungi (Deacon, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Forest soil likely represents the utmost reservoir of fungi (Deacon, 2009). According to their functions, fungi play a vital role in many forest ecosystem functions (Balami et al, 2020). The organic matter and plant litter decomposition are conducted mainly by saprotrophic fungi and thereby influencing nutrient cycling (Deacon, 2009;.…”
Section: Introductionmentioning
confidence: 99%